The historical development of geography as a subject in the schools of the Cape Province (1772-1951) - Knox, John Charles (Rhodes University, Faculty of Education, Department of Education, 1959)
As the title indicates, this is a study of the historical emergence of geography as a subject in Cape schools, and covers the period 1772-1951. The account is not merely descriptive and factual, for wherever possible an attempt is made to assess the nature and scope of the geography which was taught at different periods in relation to modern, authoritative ideas concerning the pedagogic application of the subject in the school. The work as a whole is predominantly concerned with the historical development of geography in the secondary school. However, in the initial four chapters the slight and insubstantial nature of the available data precludes the possibility of differentiating between geoeraphy of primary standard and that of secondary standard, and in these early chapters all references to the subject are consequently generalized. In Chapter 5, which deals with the period during which Langham Dale was Superintendent-Genera l of Education, geography of secondary standard becomes distinguishable from that of primary standard for the first time, and from this point onwards the two are differentiated to the fullest extent possible, and the former is chiefly emphasized. The entire study is presented against a broad background of relevant, educational developments of a general nature.
Keywords: Geography -- Study and teaching -- South Africa -- Cape of Good Hope